Observer l’autoscopie - Stéphane Olivesi (Communication)
Union leaders regard communication as an issue because of its strategically important effect on militant action. The author questions the contents and pedagogical appropriateness of a popular method of self-confrontation called autoscopy as part of current adult education programs. Contrary to its declared objective, the method ultimately turns the participating union representatives into communication dullards.